PAM 43.689 frag. 33 (IAA Plate 90 frags. 86-88) Identified as a 4Q1 (4QGen-Exoda) fragment (Gen 32:29-30?) - Tigchelaar, Eibert (Zenodo, 2021)
Identification of a 4Q1 fragment
Keywords: Dead Sea Scrolls; 4Q1